Benefits of laparoscopic liver resection for liver tumors in obese patients: a meta-analysis - Zhang, Jie; Zeng, Cuifang; Chen, Rui (Frontiers in Oncology, 2024)
ObjectiveThe superiority of laparoscopic liver resection (LLR) and open liver resection (OLR) in obese patients remains controversial. The study aims to assess the available literature and compare the perioperative outcomes of LLR and OLR for liver tumors in obese patients.MethodsWe searched PubMed, Cochrane Library, Embase, and Web of Science databases for studies comparing LLR and OLR. Odds ratios (ORs) and mean differences (MDs) with 95% confidence intervals (CIs) were calculated.ResultsNine studies were included, with a total of 1116 patients (LLR group: 482 patients; OLR group: 634 patients). Compared with OLR, LLR has lower overall morbidity (OR 0.47, 95% CI 0.34, 0.64), major complications (OR 0.45, 95% CI 0.25, 0.82), surgical site infection (OR 0.18, 95% CI 0.07, 0.48), bile leak (OR 0.45, 95% CI 0.22, 0.95), less blood loss (MD, -329.12 mL; 95% CI, -623.35, -34.88), and shorter length of stay (MD, -5.20 days; 95% CI, -7.43, -2.97). There were no significant differences in mortality, operation time, liver failure, and blood transfusion between the two groups.ConclusionsLLR for obese patients is safe and feasible. Compared to OLR, it offers better short-term outcomes. Further randomized controlled trials to verify the potential advantages of LLR over OLR are warranted.